Development And Performance Characteristics Of A Swirl Combustor Operating On VCO-Blended Fuels - Yusri, Muhammed Aqel (Universiti Sains Malaysia, 2018)
Swirl combustor have been known to enhance a combustion by supplying more air on the combustion so that the combustion rate will increase. However, there are many type of fuels that can be used in combustion. In this work, multiple ratio of mixture of fuels between vegetable cooking oil (VCO) and kerosene that being used in the swirl combustor has been study to determine the performance of the fuels and the combustor by obtaining the temperature reading during combustion. A simple swirl combustor of two air inlet which are opposite to each other and tangential to the combustion chamber are modelled in CAD to be analyse in simulation software, ANSYS and being test experimentally by implying different ratio between the mixture of VCO and kerosene fuel and the fuel-air equivalence ratio. The velocity profile and temperature distribution in the combustion chamber is then analysed and discussed. The simulation from ANSYS were using the same parameter as the experimental one which were then being compare the result with these two methods. Result from experimental analysis shows that the swirl combustor able to increase the performance of the combustion at lean mixture with highest temperature recorded is at around 0.73 to 0.81 air equivalence ratio which is at lean mixture. Rich mixture of the combustion were also tested and proved that is has lower temperature than the lean mixture. However, going lower on air equivalence ratio until about 0.6 will cause a significance drop in temperature. From the simulation analysis, it shows that air equivalence ratio of 0.6 still could produce temperature as high as air equivalence of 0.73 to 0.81. However, lower temperature were still recorded on lean mixture of the combustion which is the same as the experimental analysis.